Climate impacts on the cost of solar energy. (July 2016) - Flowers, Mallory E.; Smith, Matthew K.; Parsekian, Ara W.; Boyuk, Dmitriy S.; McGrath, Jenna K.; Yates, Luke
Abstract: Photovoltaic (PV) Levelized Cost of Energy (LCOE) estimates are widely utilized by decision makers to predict the long-term cost and benefits of solar PV installations, but fail to consider local climate, which impacts PV panel lifetime and performance. Specific types of solar PV panels are known to respond to climate factors differently. Mono-, poly-, and amorphous-silicon (Si) PV technologies are known to exhibit varying degradation rates and instantaneous power losses as a function of operating temperature, humidity, thermal cycling, and panel soiling. We formulate an extended LCOE calculation, which considers PV module performance and lifespan as a function of local climate. The LCOE is then calculated for crystalline and amorphous Si PV technologies across several climates. Finally, we assess the impact of various policy incentives on reducing the firm's cost of solar deployment when controlling for climate. This assessment is the first to quantify tradeoffs between technologies, geographies, and policies in a unified manner. Results suggest crystalline Si solar panels as the most promising candidate for commercial-scale PV systems due to their low degradation rates compared to amorphous technologies. Across technologies, we note the strong ability of investment subsidies in removing uncertainty and reducing the LCOE, compared to production incentives. Highlights: We integrate local climate into the Levelized Cost of photovoltaic technology. Climate dictates panel degradation rates and the impact of temperature on efficiency. We compare LCOE under policy scenarios for three technologies in four U. S. states. Degradation is highly variable, increasing costs by shortening panel life in many regions. Incentives targeting investment are most effective at reducing solar deployment costs.